The Role of Financial Development on Foreign Direct Investment in ASEAN-5 Countries: Panel Cointegration with Cross-Sectional Dependency Analysis - Elya Nabila Abdul Bahri; Abu Hassan Shaari Md Nor; Nor Hakimah Haji Mohd Nor (Asian Academy of Management Journal of Accounting and Finance, 2018)
This paper investigates the impact of the financial development on foreign direct investment (FDI) inflows in ASEAN-5 countries over the period of 1980–2013. The 5 countries included in this study are Malaysia, Thailand, Indonesia, Singapore and Philippines. In the model, financial development, consumer price index (CPI) and real gross domestic product (GDP) per capita are the independent variables. The stationarity of the variables is examined through both first- and second-generation unit root tests with the cross-sectional dependence among countries. The Pedroni and Westerlund cointegration tests results show the existence of long run relationship among the variables. Long term coefficients are estimated using Fully Modified Ordinary Least Square (FMOLS) model and it reveals that financial development has a nonlinear relation with FDI. When financial development passes the threshold point at above 70 point, it will benefit the FDI. Furthermore, the Panel Vector Error Correction Model (VECM) is applied to examine the causality relationship among the associated variables. The causality analysis confirms the presence of both long- term relationship and short term dynamic among the FDI, financial development, CPI and real GDP per capita.